Benthic polychaete diversity patterns and community structure in the Whittard Canyon system and adjacent slope (NE Atlantic). (December 2015) - Gunton, Laetitia M.; Neal, Lenka; Gooday, Andrew J.; Bett, Brian J.; Glover, Adrian G.
Abstract: We examined deep-sea macrofaunal polychaete species assemblage composition, diversity and turnover in the Whittard Canyon system (NE Atlantic) using replicate megacore samples from three of the canyon branches and one site on the continental slope to the west of the canyon, all at 3500 m water depth. A total of 110 polychaete species were recorded. Paramphinome jeffreysii was the most abundant species (2326 ind. m −2 ) followed by Aurospio sp. B (646 ind. m −2 ), Opheliidae sp. A (393 ind. m −2 ), Prionospio sp. I (380 ind. m −2 ), and Ophelina abranchiata (227 ind. m −2 ). Species composition varied significantly across all sites. From west to east, the dominance of Paramphinome jeffreysii increased from 12.9% on the slope to 39.6% in the Eastern branch. Ordination of species composition revealed that the Central and Eastern branches were most similar, whereas the Western branch and slope sites were more distinct. High abundances of P. jeffreysii and Opheliidae sp. A characterised the Eastern branch of the canyon and may indicate an opportunistic response to a possible recent input of organic matter inside the canyon. Species richness and diversity indices were higher on the slope compared with inside the canyon, and the slope site had higher species evenness. Within the canyon, species diversity between branches was broadly similar. Despite depressed diversity within the canyon compared with the adjacent slope, the fact that 46 of the 99 polychaete species found in the Whittard Canyon were not present on the adjacent slope suggests that this feature may enhance the regional species pool. However, our sampling effort on the adjacent slope was insufficient to confirm this conclusion. Highlights: Polychaete species diversity analysed at 3500 m in Whittard Canyon and on slope. A total of 110 polychaete species were recorded. Alpha diversity was similar inside the canyon branches and higher on the slope. Species assemblages varied significantly across the study sites from east to west. Canyon samples yielded 46 species that did not occur at the slope site, suggesting that the canyon may enhance regional diversity.